Sea clutter scattering, the K distribution and radar performance - Ward, Keith D.; Tough, Robert J. A.; Watts, Simon 1949- (Institution of Engineering and Technology, 2006)
This book provides an authoritative account of the current understanding of radar sea clutter, describing its phenomenology, EM scattering and statistical modelling and simulation, and their use in the design of detection systems and the calculation and practical evaluation of radar performance. The book pays particular attention of the component K distribution model developed by the authors during the past 20 years. The evidence for this model, its mathematical formulation and development and practical application to the specification, design and evaluation of radar systems are all discussed. In addition, the book sets the previously empirical development of the K distribution model in the wider context of recent advances in the calculation of low grazing angle electromagnetic scattering and oceanographic modelling of the statistics of the sea surface.